2017
DOI: 10.1186/s12886-017-0418-2
|View full text |Cite
|
Sign up to set email alerts
|

Iridoschisis: a case report and literature review

Abstract: Background: Iridoschisis is a rare condition that is characterized by the separation of the iris stroma into layers, with portions of the anterior layer floating freely in the aqueous humour. Here, we report three cases of iridoschisis that were complicated by either a cataract or glaucoma. Based on these cases, we speculate that the scope of iridoschisis has a rare association with intraocular pressure and the loss of corneal endothelial cells after surgery, which is mainly due to the surgery and not iridocor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
18
0

Year Published

2018
2018
2025
2025

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(18 citation statements)
references
References 15 publications
0
18
0
Order By: Relevance
“…Since iridoschisis occurs more frequently between the fifth and seventh decade of life, and patients of this age group require cataract surgery more often, it is a possibility that in these patients, iridoschisis is exacerbated and causes postoperative complications such as bullous keratopathy. 3,[7][8][9] Loewenstein et al have proposed that iridoschisis could be the result of a trauma, which alters the fibers and could lead to the division of the anterior and posterior stroma of the iris. 3 In the differential diagnosis of this patient, we discarded two other main abnormalities of the iris stroma, the iridocorneal endothelial syndrome, and the Axenfeld-Rieger syndrome.…”
Section: Discussionmentioning
confidence: 99%
“…Since iridoschisis occurs more frequently between the fifth and seventh decade of life, and patients of this age group require cataract surgery more often, it is a possibility that in these patients, iridoschisis is exacerbated and causes postoperative complications such as bullous keratopathy. 3,[7][8][9] Loewenstein et al have proposed that iridoschisis could be the result of a trauma, which alters the fibers and could lead to the division of the anterior and posterior stroma of the iris. 3 In the differential diagnosis of this patient, we discarded two other main abnormalities of the iris stroma, the iridocorneal endothelial syndrome, and the Axenfeld-Rieger syndrome.…”
Section: Discussionmentioning
confidence: 99%
“…However, some researchers suggested that iridoschisis is not inherited but occurs sporadically, secondary to trauma, glaucoma or syphilis [ 2 , 6 , 7 , 8 , 9 ]. Other authors considered iridoschisis age-related atrophy, given that the condition is found predominantly in persons between 60 and 70 years of age [ 10 ]. As reviewed by Mansour, the mean and median ages of 131 patients with iridoschisis were 57 years and 62 years, respectively.…”
Section: Epidemiology and Inheritancementioning
confidence: 99%
“…Anterior segment optical coherence tomography (AS-OCT), ultrasound biomicroscopy (UBM) and Scheimpflug imaging are complementary diagnostic options in patients with suspected iridoschisis. ( Figure 3 ) [ 10 , 27 , 28 ]…”
Section: Clinical Characteristics and Diagnostic Imagingmentioning
confidence: 99%
“…In 2003, Ghanem et al used a vitreous cutter to trim fibres, 31 whereas Chen et al cut the anterior fibres using Vannas scissors. 11 We describe a novel, low-risk, inexpensive microcautery approach to free-fibre management iridoschisis. We also outline principles for minimizing risk during cataract surgery in the setting of iridoschisis.…”
Section: Novel Approaches To Phacoemulsification In Iridoschisismentioning
confidence: 99%
“…Although Chen et al suggest that there is no need for pupil stabilization, 11 these patients have unstable irides by nature because the iris architecture is disrupted. Furthermore, we have noted poorly dilating pupils in patients with iridoschisis.…”
Section: Novel Approaches To Phacoemulsification In Iridoschisismentioning
confidence: 99%